Putative prefoldin complex subunit 5 of Plasmodium berghei is crucial for microtubule formation and parasite development in the mosquito - Beyeler, Raphael Nicola; Jordan, Melanie; Dorner, Lilian; He, Buyuan; Cyrklaff, Marek; Roques, Magali; Stanway, Rebecca; Frischknecht, Friedrich; Heussler, Volker (Molecular microbiology, 2024)
Plasmodium sporozoite development in and egress from oocysts in the Anopheles mosquito remains largely enigmatic. In a previously performed high-throughput knockout screen, the putative subunit 5 of the prefoldin complex (PbPCS5, PBANKA_0920100) was identified as essential for parasite development during mosquito and liver stage development. Here we generated and analyzed a PbPCS5 knockout parasite line during its development in the mosquito. Interestingly, PbPCS5 deletion does not significantly affect oocyst formation but leads to a growth defect resulting in aberrantly shaped sporozoites. Sporozoites produced in the absence of PbPCS5 were thinner, markedly elongated, and did, in most cases, not contain a nucleus. Sporozoites contained fewer subpellicular microtubules, which reached deep into the sporoblast during sporogony where they contacted and indented nuclei. These aberrantly shaped sporozoites did not reach the salivary glands, and we, therefore, conclude that PbPCS5 is essential for sporogony and the life cycle progression of the parasite during its mosquito stage.
Veröffentlicht: 27 November 2023
Gesehen am 12.01.2024